A journey into a Mediterranean diet and type 2 diabetes: a systematic review with meta-analyses. Issue 8 (10th August 2015) - Esposito, Katherine; Maiorino, Maria Ida; Bellastella, Giuseppe; Chiodini, Paolo; Panagiotakos, Demosthenes; Giugliano, Dario
Abstract : Objectives: To summarise the evidence about the efficacy of a Mediterranean diet on the management of type 2 diabetes and prediabetic states. Design: A systematic review of all meta-analyses and randomised controlled trials (RCTs) that compared the Mediterranean diet with a control diet on the treatment of type 2 diabetes and prediabetic states was conducted. Electronic searches were carried out up to January 2015. Trials were included for meta-analyses if they had a control group treated with another diet, if they were of sufficient duration (at least 6 months), and if they had at least 30 participants in each arm. A random-effect model was used to pool data. Participants: Adults with or at risk for type 2 diabetes. Interventions: Dietary patterns that described themselves as using a 'Mediterranean' dietary pattern. Outcome measures: The outcomes were glycaemic control, cardiovascular risk factors and remission from the metabolic syndrome. Results: From 2824 studies, 8 meta-analyses and 5 RCTs were eligible. A 'de novo' meta-analysis of 3 long-term (>6 months) RCTs of the Mediterranean diet and glycaemic control of diabetes favoured the Mediterranean diet as compared with lower fat diets. Another 'de novo' meta-analysis of two long-term RCTs showed a 49% increased probability of remission from the metabolic syndrome. 5 meta-analyses showed a favourable effect of the Mediterranean diet, as compared with other diets, on body weight, total cholesterol and high-density lipoprotein cholesterol. 2 meta-analyses demonstrated that higher adherence to the Mediterranean diet reduced the risk of future diabetes by 19–23%. Conclusions: The Mediterranean diet was associated with better glycaemic control and cardiovascular risk factors than control diets, including a lower fat diet, suggesting that it is suitable for the overall management of type 2 diabetes.